2011
DOI: 10.1371/journal.pbio.1000589
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis of Response Regulator Dephosphorylation by Rap Phosphatases

Abstract: Crystallographic, biochemical, and genetic studies reveal the mechanism of Rap protein phosphatase activity within the phosphorelay pathway leading to sporulation in Bacillus species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
176
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(186 citation statements)
references
References 50 publications
9
176
1
Order By: Relevance
“…In previous studies, the concave surface of the repeat domain of peptide pheromone receptors was identified as the pheromone-binding site (Fig. S5 A-D) (13,14,(16)(17)(18). We hypothesized that the Streptococcus Rgg receptors similarly used the concave surface of their repeat domain as the SHP-binding site.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…In previous studies, the concave surface of the repeat domain of peptide pheromone receptors was identified as the pheromone-binding site (Fig. S5 A-D) (13,14,(16)(17)(18). We hypothesized that the Streptococcus Rgg receptors similarly used the concave surface of their repeat domain as the SHP-binding site.…”
Section: Resultsmentioning
confidence: 92%
“…A search (30) of the PDB database for proteins structurally similar to Rgg2 Sd identified PrgX (PDB ID code 2AXZ, Z score = 19.2) (18), PlcR (PDB ID code 3U3W, Z score = 13.1) (15), NprR (PDB ID code 4GPK, Z score = 11.7) (19), and RapI (PDB ID code 4I1A, Z score = 10.7) (17). In previous studies, the concave surface of the repeat domain of peptide pheromone receptors was identified as the pheromone-binding site (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the structure, the side chain of RapH Gln-47 inserts into the Spo0F active site. RapH Gln-47 may orient water for direct in-line hydrophilic attack on the Spo0F phosphoaspartate 54 phosphorous atom and thus cause hydrolysis of the phosphoryl group (54). In these cases, the interactions are primarily responsible for the specific histidine kinase-response regulator or connector-response regulator binding.…”
Section: Discussionmentioning
confidence: 99%
“…1) (8,9). In addition to RapA and RapB, many other Rap proteins, including RapE, RapH, and RapJ, function similarly to dephosphorylate Spo0F (10)(11)(12). The ultimate effect of dephosphorylating Spo0F is a decrease in the cellular concentration of phosphorylated Spo0A (Spo0AϳP).…”
mentioning
confidence: 99%